Information Revealed through the Regulatory Process: Interactions between the SEC and Companies ahead of Their IPO. (27th January 2020) - Lowry, Michelle; Michaely, Roni; Volkova, Ekaterina
Abstract: We analyze communications between the SEC and firms prior to IPOs using LDA analysis and KL divergence. The SEC's concerns closely map onto the regulator's stated mandate: companies increase prospectus disclosures on precise topics of SEC concern. Revenue recognition is the dominant topic of SEC concern, and it is not independently discovered by investors. Increased SEC concern about it is associated with greater secondary sales, lower post-IPO liquidity, lower post-IPO returns, and a higher probability of withdrawal. The regulator's role during the capital raising process results in increased transparency but contributes to delays in the going public process.